2009
DOI: 10.3832/efor0598-006
|View full text |Cite
|
Sign up to set email alerts
|

Deadwood in Italian forests according to National Forest Inventory results

Abstract: IntroduzioneFino a poco tempo fa il legno morto nei boschi ve niva considerato dai tecnici forestali e da parte della popolazione un segno di cattiva gestione, per gli ef fetti relativi a possibili attacchi di parassiti, allo svi luppo di incendi o semplicemente per motivi di na tura estetica (Schiegg 1998). Oggi, pur non essendo trascurabili questi aspetti in particolari situazioni, al legno morto viene riconosciuto un ruolo fondamen tale per la conservazione della biodiversità dell'eco sistema, e la sua pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…This lack of harmonization leads to a flaw in the comparison of different studies [40] or data sources. As an example, within the National Forest Inventories (NFI) of some European countries, the distinction between CWD and FWD is made according to a threshold of 10 cm in Scandinavian countries (Sweden, Norway, and Finland) and Italy, 7 cm in Switzerland and France, and 20 cm in Austria and Germany [11].…”
Section: Deadwoodmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of harmonization leads to a flaw in the comparison of different studies [40] or data sources. As an example, within the National Forest Inventories (NFI) of some European countries, the distinction between CWD and FWD is made according to a threshold of 10 cm in Scandinavian countries (Sweden, Norway, and Finland) and Italy, 7 cm in Switzerland and France, and 20 cm in Austria and Germany [11].…”
Section: Deadwoodmentioning
confidence: 99%
“…Deadwood also plays a fundamental role in the carbon balance of forest ecosystems. Due to its increasing importance, National Forest Inventories (NFI) worldwide are now progressively including deadwood as a target component and its quantification is becoming of great interest [7][8][9][10][11][12][13]. Countries with a longer tradition of productive forestry are already assessing the impacts of biomass exploitation and strict production management [14][15][16][17], and their effect on deadwood presence.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, results obtained in unharvested forests from decades (PACI and SALBITANO, 1998;PIOVESAN et al, 2005;MOTTA and EDOUARD, 2005;MOTTA et al, 2006;MARCHETTI et al, 2010), revealed a high variability of deadwood occurrence, with values similar to those here reported. On the contrary, the volume of deadwood generally occurring in Italian forests (mainly managed forest) is markedly lower: the National forest Inventory (INFC, 2005;PIGNATTI et al, 2009) estimates deadwood occurrence in Italy on average equal to 8.8 m 3 ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…La quantità di biomassa è maggiore in Europa centrale rispetto alle foreste boreali ed alle foreste mediterranee. In Italia secondo l'INFC (2005), il volume medio di CWD presente nei nostri boschi ammonta a 8.8 m 3 ha -1 (Pignatti et al 2009). Questo quantitativo è maggiore nelle foreste di alto fusto rispetto alle foreste governate a ceduo ed è maggiore nei boschi di conifere rispetto ai boschi di latifoglie.…”
Section: Quanta Necromassa è Presente Nelle Nostre Foreste?unclassified